The Effect of Listening to Quran Recitation on Score of Post-Stroke Fatigue in Acute Ischemic Stroke Patients - Silviana, Meyvita; Riasari, Naili Sofi; Mantikha, Farah Febriyani (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: One of the common stroke complications is post-stroke fatigue (PSF) with the prevalence of 25–85%. PSF influences health-related quality of life, disability, dependence in daily activities, ability to return to work, and case fatality rate of stroke patients. Listening to Quran recitation can increase alpha waves in the brain, reduce stress and inflammatory biomarkers. AIM: The purpose of this study was to identify the effect of listening to Quran recitation on PSF and find out the mean Fatigue Assessment Scale (FAS) score in acute ischemic stroke patients. METHODS: This was an experimental study with one-group pretest-posttest design. Sixteen subjects were recruited by consecutive sampling in Sultan Agung Islamic Hospital, Semarang. The FAS score was assessed on the 1st day of study, then Quran recitation was played 2 sessions a day, 15 min/session, for 5 days. The FAS score was reassessed on the last day. The study was conducted from August to September 2021. The analysis test used was paired t-test. RESULTS: The results showed a significant relationship between listening to Quran recitation with changes in FAS score in acute ischemic stroke patients (p < 0.05). Most of the subjects were <65 years old, male, had hypertension, did not have DM, and did not smoke. CONCLUSION: Listening to Quran recitation had an effect on changes in FAS score.